Singing by and with heart: embodying Candomblé’s sensuous knowledge through songs and dances in Berlin (Orfeu, 2018)
By means of ethnographic fieldwork in Berlin and Recôncavo da Bahia, my Ph.D. research sought to disclose transcultural and subjective processes involved in the embodiment of the Afro-Brazilian religion of Candomblé, having my own body as a point of departure. This article presents some results regarding the transmission of ritual songs and dances at “Ilê Obá Sileké”, Germany’s only house for the practice of Candomblé. Despite the distance from the original cultural context, the priest and further masters emphasize the value of learning through practice. In other words, through body engagement instead of verbal communication and instruction. This implies mimetic processes envolving the whole subjective dimension of learning and hence of the sensible knowledge acquired. In Candomblé transmission, I argue, it is neither technical precision nor intelectual and semantic understanding of the songs and gestures that have primacy, but rather the conveyance of their “emotional essence” (Merleau-Ponty 1945): the bodily experience of sharing this very essence with the community, as well as with the gods, the orixás.
Keywords: bodily learning; sensuous knowledge; Afro-Brazilian music; Candomblé; embodiment